(untitled) (Jurnal Pembangunan Sosial, 2015)
This research focuses on Pengkid. Pengkid is a term or a slang used in Malaysia to refer to lesbians in the butch category. They are a group of individuals who practices same sex sexual orientation, in which they are sexually attracted to women. This research was conducted to examine interpersonal relationships of Pengkid and their satisfaction over these relationships. To gain a deeper and more comprehensive picture, a semi-structural interview was conducted with 25 Pengkid participants from around Pulau Pinang, Kuala Lumpur, and Selangor. Participants were recruited using various methods including from Malaysian Pengkid official website and through snowballing technique. Results show that Pengkids in this study have wide and various categories of interpersonal relationships and received several types of social supports from their interpersonal relationships. This indicates that Pengkid in this study were well-accepted by their social circle and maintained a good relationship with individuals who knew and are aware of their sexual orientation. Close friends and romantic partners were the main sources of all types of support for this group. Other categories of interpersonal relationships also provide some social supports to this group but of lesser quality and quantity compared to these two. Findings from this research suggest the unique and different role is played by different individuals in one social network. This study contributes to the same sex sexual orientation on this particular group.